A clinical case of a complicated course of immunoglobulin A vasculitis with long-term nephritis: peculiarities of treatment - V.O. Synytska; O.R. Boyarchuk; O.I. Greh (Zaslavsky O.Yu., 2022)
Immunoglobulin A vasculitis is the most common systemic vasculitis in children. Its course can be mild, involving only the skin and not requiring medical intervention, as well as severe, recurrent, long-lasting - when the gastrointestinal tract and kidneys are involved. Nephritis is the most often cause the disease severity, although abdominal pain usually affects the well-being of the child. We present a clinical case of immunoglobulin A vasculitis in a 6-year-old girl who had an acute onset with severe abdominal syndrome and vomiting that preceded the appearance of the rash. The use of direct anticoagulants led to gastric bleeding. Treatment with corticosteroids had a positive effect on the abdominal syndrome, but did not prevent the development of kidney injury with hematuria and moderate proteinuria. Nephritis had a stable persistent course. Recurrences of rashes and abdominal pain were observed. Long-term corticosteroid therapy and renoprotection using angiotensin-converting enzyme inhibitors allowed partial control of the disease. The presented clinical case confirms that the course of immunoglobulin A vasculitis can be long, with frequent relapses of skin manifestations, abdominal syndrome, transformation into glomerulonephritis, even in the presence of only moderate hematuria and proteinuria. Skin manifestations and nephritis cannot be always completely controlled by the first-line therapy, which requires a balanced decision regarding the escalation of treatment, taking into account biopsy data, kidney function, and severity of proteinuria. Renoprotection with angiotensin-converting enzyme inhibitors or angiotensin receptor blockers can prevent secondary kidney injury. The implementation of European guidelines in the treatment of immunoglobulin A vasculitis, including that associated with nephritis, will allow unifying the approaches to patient management, detecting kidney damage timely and carrying out appropriate treatment measures.